2023
DOI: 10.1002/glia.24358
|View full text |Cite
|
Sign up to set email alerts
|

Disrupting cortical astrocyte Ca2+ signaling in developing brain induces social deficits and depressive‐like behaviors

Abstract: Astrocytes are present throughout the central nervous system and display complex intracellular Ca 2+ signals. However, it is largely unknown regarding how astrocytic Ca 2+ signals regulate neural microcircuits in developing brain and mammalian behavior in vivo. In this study, we specifically overexpressed the plasma membrane calciumtransporting ATPase2 (PMCA2) of cortical astrocytes and used immunohistochemistry, Ca 2+ imaging, electrophysiology, and behavioral tests to investigate the effects of genetically r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…On the contrary, the general picture in humans diagnosed with major depressive disorder seems to be a reduction in astrocyte density in the cerebral cortex (Cobb et al, 2016;O'Leary et al, 2021;Rajkowska & Stockmeier, 2013), but astrocyte hypertrophy has also been reported (Torres-Platas et al, 2011); this points to the possibility that dysregulation rather than absolute levels of cortical astrocyte activity and density may induce a depressive phenotype. Recent data suggest that disruption of cortical astrocyte calcium-signaling induces a depressive-like behavior accompanied by synaptic structure abnormalities in mice (Luo et al, 2023), which may be part of the mechanistic explanation linking astrocytes to depression. Another CKO mouse model, generated by use of a Cre-construct driven by the CamKII-promoter to knock out Bmal1 in all regions of the forebrain, while cellularly limiting the deletion to excitatory neurons, did not exhibit any affective symptoms (Snider et al, 2016).…”
Section: Gfap-and Fabp7-positive Cells Are Abundant In the Cerebral C...mentioning
confidence: 99%
“…On the contrary, the general picture in humans diagnosed with major depressive disorder seems to be a reduction in astrocyte density in the cerebral cortex (Cobb et al, 2016;O'Leary et al, 2021;Rajkowska & Stockmeier, 2013), but astrocyte hypertrophy has also been reported (Torres-Platas et al, 2011); this points to the possibility that dysregulation rather than absolute levels of cortical astrocyte activity and density may induce a depressive phenotype. Recent data suggest that disruption of cortical astrocyte calcium-signaling induces a depressive-like behavior accompanied by synaptic structure abnormalities in mice (Luo et al, 2023), which may be part of the mechanistic explanation linking astrocytes to depression. Another CKO mouse model, generated by use of a Cre-construct driven by the CamKII-promoter to knock out Bmal1 in all regions of the forebrain, while cellularly limiting the deletion to excitatory neurons, did not exhibit any affective symptoms (Snider et al, 2016).…”
Section: Gfap-and Fabp7-positive Cells Are Abundant In the Cerebral C...mentioning
confidence: 99%